Measuring Post-transfusion Recovery and Survival of Red Blood Cells: Strengths and Weaknesses of Chromium-51 Labeling and Alternative Methods - Roussel, Camille; Buffet, Pierre A.; Amireault, Pascal (Frontiers in Medicine, 2018)
The proportion of transfused red blood cells (RBC) that remain in circulation is an important surrogate marker of transfusion efficacy, and contributes to predict the potential benefit of a transfusion process Over the last 50 years, most of the transfusion recovery data were generated by 51Cr-labeling studies, and were predominantly performed to validate new storage systems and new processes to prepare RBC concentrates. As a consequence, our understanding of transfusion efficacy is strongly dependent on the strengths and weaknesses of 51Cr-labeling in particular. Other methods such as antigen mismatch or biotin-based labeling can bring relevant informations, for example on the long-term survival of transfused RBC. These radioactivity-free methods can be used in patients including from vulnerable groups. We provide an overview of the methods used to measure transfusion recovery in humans, compare their strengths and weaknesses and discuss their potential limitations. Also, based on our understanding of the spleen-specific filtration of damaged RBC and historical transfusion recovery data, we propose that RBC deformability and morphology are storage lesion markers that could become useful predictors of transfusion recovery. Transfusion recovery can and should be accurately explored by more than one method. Technical optimization and clarification of concepts is still needed in this important field of transfusion and physiology.